2017
DOI: 10.1016/j.diabres.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pregnancy weight change and incidence of gestational diabetes mellitus: A finding from a prospective cohort study

Abstract: Aims: In a population-based cohort study we examined the associations between early adult pre-pregnancy weight change and the risk of gestational diabetes mellitus (GDM). Methods:The study included 3,111 women from the 1973-78 cohort of the Australian Longitudinal Study on Women's Health. These women have been surveyed regularly since 1996. Women without diabetes and GDM were followed-up between 2003 and 2012.Generalized estimating equations were used to assess the effect of baseline (1996, mean age 20 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…With respect to the prevalence of GDM, the results of this study are consistent with previous findings . However, only a few previous studies have focused on the risk of GDM in primiparous women .…”
Section: Discussionsupporting
confidence: 91%
“…With respect to the prevalence of GDM, the results of this study are consistent with previous findings . However, only a few previous studies have focused on the risk of GDM in primiparous women .…”
Section: Discussionsupporting
confidence: 91%
“…The major strength of this study was the availability of RBC folate levels during the second trimester of pregnancy in a Chinese population. Notably, previous studies have suggested that BMI before pregnancy and excessive weight gain in pregnancy are associated with the increased risk of GDM (Adane, Tooth, & Mishra, ; MacDonald, Bodnar, Himes, & Hutcheon, ). In the current study, we did not include these factors in our adjusted models, although maternal age, parity, and BMI at enrollment were adjusted.…”
Section: Discussionmentioning
confidence: 99%
“…Cho, Hur, and Lee () found significant correlations between GWG in the early stages of pregnancy and GDM, gestational hypertension, large‐for‐gestational‐age births, macrosomia, and primary cesarean delivery. Adane, Tooth, and Mishra () found that compared with women whose GWG was steady, women with underweight or average prepregnancy BMIs had a 2.7 times higher risk of developing GDM when their GWG became moderate or high (>2.5% per year).…”
Section: Introductionmentioning
confidence: 99%